(untitled) (Journal of Civil Engineering Researchers, 2024)
This study investigates and compares the performance of reinforced concrete buildings containing SMA bars and steel bars as longitudinal reinforcement of column.The use of this type of material is to reduce permanent deformation in the structure due to the reversible properties of these materials.First, a laboratory specimen of a reinforced concrete column with shape memory alloy bars was modeled in the OPENSEES software and the modeling method was validated.Then, 3- and 5-story concrete frames, in two states, reinforced with steel bars and SMA bars, under nonlinear static and nonlinear time history analyses with near-fault records were analyzed.The results of the time history analyses showed that, although the use of SMA bars significantly reduces the residual deformation of the structure, it does not show a significant effect on reducing the maximum displacement of the structure.The maximum rotational deformation of columns in frames with SMA bars is greater than of frames with steel bars.However, SMA bars have greatly reduced the permanent rotational deformation of columns and reduced it to zero.The maximum drift of floors in frames with SMA bars increases slightly.The permanent drift of the structure in frames with SMA bars is significantly reduced.